Marine n‐3 fatty acids and cognitive change among older adults in the VITAL randomized trial - Jae H. Kang; Chirag M. Vyas; Olivia I. Okereke; Soshiro Ogata; Michelle Albert; I‐Min Lee; Denise D'Agostino; Julie E. Buring; Nancy R. Cook; Francine Grodstein; JoAnn E. Manson (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction : Few large, randomized trials have evaluated marine n‐3 supplements and cognition in healthy older adults. Methods : Healthy community‐dwelling participants aged 60+ years (mean [standard deviation] = 70.9 [5.8] years) in VITAL (randomized trial of n‐3 fats [1 g/day, including 840 mg of eicosapentaenoic acid + docosahexaenoic acid] and vitamin D) were included: 3424 whose cognition was assessed by phone (VITAL‐Cog; eight neuropsychological tests; 2.8 years) and 794 evaluated in person (CTSC‐Cog; nine tests; 2.0 years). The primary outcome was a global score (average of test z‐scores) of change over two assessments. We used multivariable‐adjusted linear mixed models; substudy‐specific results were meta‐analyzed. Results : We observed no significant effect of n‐3 supplementation: the mean difference in annual rate of cognitive change for the n‐3 versus placebo group was –0.01 standard units (95% confidence interval [CI]: –0.02, 0.003) in VITAL‐Cog and –0.002 (95% CI: –0.04, 0.03) in CTSC‐Cog; the pooled difference was –0.01 (95% CI: –0.02, 0.003; P = .15). Discussion : Marine n‐3 supplementation (1 g/day) did not confer cognitive benefits over 2 to 3 years in community‐dwelling older adults.